GAMBARAN PENYEBAB TERJADINYA PEMBENGKAKAN PAYUDARA PADA IBU MENYUSUI DI POLINDES DESA MEDDELEN KECAMATAN LENTENG - Emdat Suprayitno; Iva Gamar Dia Pratiwi; Zakiyah Yasin (Wiraraja Medika : Jurnal Kesehatan, 2018)
Breast swelling occurs because breast milk is not sucked by the baby adequately, so therest of the milk is collected in the duct system that resulted in swelling and Asi Dam. Static bloodvessels and lymphs will result in increased intraductal pressure affecting the various segments ofthe breast, resulting in increased breast pressure. It can also occur due to a blockage in the milkducts.This study aims to determine the description of the causes of breast engorgement inPolindes Tunas Bunda Meddelan Village District Lenteng Sumenep Year 2015 The method used isdescriptive research method, that is to know the description of causes of breast engorgement inMeddelan village Lenteng District Sumenep Regency 2015. Population in this research is as manyas 25 breastfeeding mothers and the sample is total sampling. And the method of collecting databy using questionnaire. The data were analyzed with the frequency distribution in percentage (%).The results of the study on June 12, 2015 showed that of 25 breastfeeding mothers nearlyhalf of the respondents had a severe stress level of 8 (32%), almost half of respondents appliedless than 12 (48%) breastfeeding techniques, almost all respondents did breast care the less asmany as 19 (76%), almost half of respondents had mild breast swelling that is as much as 10(40%).From the results of the study researchers suggest for the community, especiallybreastfeeding mothers in order to keep personal hygiene or breast care to prevent the occurrenceof blockage and eventually experience breast engorgement.